Non-invasive protection of shear critical nonseismically detailed RC beam-column joints against seismic loading - Rao, G. Appa; Gangaram, M. (Journal of Structural Engineering, 2024)
In this study an effort has been made to protect the shear critical nondetailed reinforced concrete beam-column joints by providing bracing elements for altering the joint mechanics under lateral loading. The beam-column joints play key role for imparting the global response of RC framed structures that are built during the early 1950’s through 1970’s, which do not possess adequate shear strength and ductility against the lateral loads. Majority of the conventional retrofit schemes are partially effective in preventing the failure of joints. A non-invasive scheme by altering the joint mechanics has been proposed to prevent the joint reaching its shear failure by shifting the formation of plastic hinges in the beams. The studies were carried out on the effect of Knee bracing or haunch element for the optimum location and orientation to achieve the maximum reduction of joint shear stress. The location of the knee bracing or haunch element was varied from 0.1 to 0.5 times the beam span at an inclination varying between 15° and 60°. It has been found that the joint shear stress was signifi cantly reduced at 45° angles at a location of 0.2 times the beam span.